Fractional CO2 laser, platelet rich plasma and combination of both in treatment of female pattern hair loss - Abeer Tawfik; Noha Gahdan; Moataz Nosseir (Journal of the Egyptian Women’s Dermatologic Society)
Background Female pattern hair loss (FPHL) is one of the most common chronic problems seen by dermatologists worldwide. Hair loss has a significant influence on the quality of life and is associated with low self-esteem and depression. The treatment modalities vary from medical approaches to surgical interventions. However, limited perceived efficacy of a therapeutic regimen may lead to premature stoppage of treatment. Objective To evaluate the efficacy of platelet rich plasma (PRP), fractional CO2 laser and combination of both in treatment of FPHL. Patients and methods This is a split-scalp prospective interventional study in which thirty patients presenting with FPHL received PRP in one area, fractional CO2 in another one, combined fractional CO2 and PRP in a third one and saline intradermal injection in the fourth area in frontal and mid scalp region of scalp. The sessions were scheduled every 2 weeks for 4 sessions, then monthly for 2 months. Patients were evaluated after each session and 3months after the last session. The results were evaluated by trichoscopic and folliscopic examination in the four examined areas. Assessment of treatment response was done according to the count of terminal and vellus hair, the thickness and density of hair shafts and the percentage of change, determined by folliscopic examination. Patients’ satisfaction and side effects were evaluated. Results There was significant difference between the studied groups as regards percentage of change of terminal hair, vellus hair, hair thickness and hair density after treatment. Pairwise comparisons showed that the combined group was statistically better than either PRP, fractional CO2, or saline group as regards all studied parameters (P value was <0.05 for each). Conclusion Combination of fractional CO2 laser and topical PRP application would have a synergistic effect in treatment of FPHL. The technique would be an excellent alternative to injections in order to stimulate hair growth in patients with FPHL.